Cadmium isotope fractionation in seawater: driving mechanisms and palaeoceanographic applications - Horner, T (2012)
The global marine distributions of Cd and phosphate are closely correlated, which has led to Cd being considered as a marine micronutrient. Recent developments in Cd stable isotope mass spectrometry have revealed that Cd uptake by phytoplankton causes isotopic fractionation in the open ocean and in culture. The explanation for this nutrient-like behaviour is unknown as there is only one identified biochemical function for Cd, an unusual Cd/Zn carbonic anhydrase (CdCA1). This thesis investigates why Cd appears to act as an algal nutrient by performing subcellular analyses of microorganisms genetically-modified to express the CdCA1 gene. It was found that CdCA1 was not a significant contributor to whole-cell Cd isotope compositions. Instead, a large proportion of the internalized Cd is sequestered into cell membranes with a similar direction and magnitude of Cd isotopic fractionation as seen in surface seawater. This observation is explained if Cd is mistakenly imported with other divalent metals and subsequently managed by binding within the cell to avoid toxicity. This result implies that surface seawater Cd isotope compositions, if captured by an appropriate archive, may be invaluable for reconstructions of past marine productivity. The role of environmental factors in modulating the inorganic partitioning of Cd isotopes into calcite was investigated through a series of laboratory analogue experiments. In seawater, the light isotopes of Cd are always preferred in calcite. The magnitude of fractionation showed no response to temperature, ambient [Mg], or precipitation rate. To further identify suitable palaeaoceanographic archives, the Cd isotopic composition of a suite of modern deep-sea corals were investigated. It was found that the Cd/Ca and Cd isotope composition of coralline calcium carbonate followed the predicted trend for closed-system Rayleigh fractionation in the calcifying space. The lack of isotopic offsets between some corals and seawater will simplify the application of Cd isotopes in deep-sea corals -- and potentially other marine calcifying organisms that vacuolize seawater prior to calcium carbonate precipitation -- to palaeoceanography.